Construction on training course and training quality evaluation index system of chronic disease medication therapy management service (MTMs) in China: A Delphi study - Wenting Cai; Yao Yao; Wenpu Lei; Huixin Li; Simin Yan; Qiuhui Wu; Jian Wang; Weihong Ge; Jinping Zhang (PLoS ONE, 2025)
Objective This study aims to construct a training course and quality evaluation index system for chronic disease Medication Therapy Management service (MTMs) that is suitable for China’s national conditions. It seeks to provide tools and a scientific foundation for assessing the quality of MTMs training. Methods Drawing from domestic and international literature and combining with the practice of chronic disease medication management by Chinese pharmacists, a preliminary framework for the evaluation index system was established. The Delphi method was used to solicit expert opinions, evaluate and improve the evaluation index system. Indicator weights were determined by using the Analytic Hierarchy Process (AHP). Results Both rounds of expert inquiry achieved a positive degree of 100% (18/18 experts). The authority coefficients (Cr) were 0.90 and 0.91 respectively. The Kendall coordination coefficients (Kendall’s W) of the second and third-level indicators for the first round of inquiry were 0.230 and 0.189, while those for the second round were 0.326 and 0.213. Finally, an MTMs training course and training quality evaluation index system was structured, comprising 3 first-level indicators, 11 second-level indicators, and 39 third-level indicators. Conclusion The evaluation index system constructed in this study is scientifically robust and rational, offering a foundation to standardize MTMs training practices effectively.